Synergistic Effect of Propolis Extract and Vitamin E on TNF-α Reduction in High Fat Diet–Induced Rats - Novitasari Anggraini; Joko Wahyu Wibowo; Hadi Sarosa (Molecular and Cellular Biomedical Sciences, 2026)
Background: High-fat diet (HFD) can lead to a low-grade inflammatory state in the body called meta-inflammation. Propolis and Vitamin E are proven to act as antiinflamatories by inhibiting the NF-Kβ pathway, inhibiting lipid peroxidation, and scavenging free radicals. TNF-α is a biomarker for the analysis of acute pro-inflammatory cytokines. This study aimed to determine the effect of propolis extract and vitamin E on TNF-α responses in HFD-induced rats.Materials and methods: A randomized controlled trial with post-test only with control group design. Thirty Wistar rats were acclimatized for 7 days, prior to randomization into five groups that are C group (standard diet), T1 group (HFD 2 mL of quail eggs/day),  T2 group (HFD + vitamin E 12mg /200 g of rat BW/day),  T3 group (HFD + propolis extract 36 mg /200 g of rat BW/day), and T4 group (HFD + vitamin E 6 mg/200 g of rat BW/day + propolis extract 18 mg/200 g of rat BW/day).  All intervention were administered orally for 14 days. TNF-α were measured from periorbital blood sample on day 15th using ELISA.Results: TNF-α highest levels was found in HFD group (T1) on 90.53±10.48 ng/L and the lowest was found in propolis group (T3) on 68.21±3.97 ng/L. Combination group (T4) has TNF-α levels on 68.46±15.39ng/L. One way ANOVA showed significant differentiation p<0.05.Conclusion: Propolis extract and vitamin E significantly reduced TNF-α levels on HFD induced rats, either in single form or in combination. This shows their rule as anti-inflammatory agent. Keywords: high fat diet, propolis extracts, TNF-α ,vitamin E